Effectiveness of PHBS Pocketbook as Intervention Media for Elementary School Students - Humairo, Mika Vernicia; Sukarno Putri, Paramytha Magdalena; Ulfah, Nurnaningsih Herya; ,, Ainna Salima; Nafisah, Azalia Fakhirotul; Lasmunifa, Sarah Sabrina Putri; Syawanah, Aquila Dzikri (Media Karya Kesehatan, 2026)
Clean and Healthy Living Behavior (PHBS) is an important effort to improve the health quality of elementary school students. This community service activity aims to improve the knowledge and behavior of PHBS students of SDN Sumbersari 03 Malang through the media of the pocket book "My Healthy Friends". The research method uses a quantitative approach with a quasi-experimental design through One Group Pretest Posttest Design for 50 students in grades III and IV with a 20-question questionnaire instrument covering seven PHBS indicators. Data analysis uses the non-parametric Wilcoxon Signed-Rank Test because the data is not normally distributed. The results show a significant increase in the median value of student knowledge from 78 at the time of the Pre-test and 91 at the time of the Post-test (p = 0.000). Descriptively, the average student score increased from 75.06 to 81.9, with the percentage of students in the "good" knowledge category increasing from 40% to 98%. Pocket books have been proven effective in improving students' knowledge, attitudes, and practices regarding clean and healthy living (PHBS) and supporting the achievement of SDGs 4 (Quality Education) and 6 (Clean Water and Sanitation).Keywords: pocket books, clean and healthy living behavior, elementary school students.